THE USE OF DEMONTRATION METHODS AND POSTER MEDIA IN INCREASING KNOWLEDGE OF DENTAL AND ORAL HEALTH OF SCHOOL AGE CHILDREN - Jean Henry Raule; Dessy F. Tuharea; Jeanne d’Arc Zavera Adam; Tati Setyawati Ponidjan; Johana Tuegeh; Lourrien G. Runtu (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2023)
Back Ground of dental health problems in children until now, is still very high. Several studies have reported that dental caries is still high and the lack of behavior to maintain dental and oral health is closely related to children's lack of knowledge. This study aims to determine the effectiveness of the demonstration method and poster media on the knowledge of school-age children about dental and oral health. Method research pre-experimental (one group pre-post test design). The sample was 40 children in grades IV and V (total sampling) at SD GMIM 28 Manado City, which were divided into 2 groups. Group A used the demonstration method, group B used Poster media. Measurement of knowledge using a questionnaire with an intervention that is health education about dental and oral health, data analysis using the Paired Sample T Test. The Results of the statistical test analysis of group A obtained the mean value before the intervention was 20.05 and after the intervention became 25.80, with a Pvalue 0.000 (< 0.05). ). Group B got the mean before the intervention 20.45 and after the intervention 25.10 with a Pvalue 0.000 (<0.05). These results indicate that there is a significant difference in children's knowledge before and after education, both using demonstration methods and poster media. Conclusion Education using demonstration methods and poster media, is effective in increasing knowledge of school age children about dental and oral health.